NEW SOWING SYSTEM FOR VARIABLE RATE INTRA SOIL APPLICATION OF MINERAL FERTILIZERS - Е. A. Zolotukhin; G. I. Lichman; S. O. Nukeshev (Сельскохозяйственные машины и технологии, 2015)
The existing sowing systems (SS) of machines for fertilizers application not fully provide quality of introduction of mineral fertilizers. Unevenness and instability of application reach 20-40 percent at demanded to 15 percent. The SS equipped with glow coil of original design was offered for ensuring necessary quality of mineral fertilizers distribution across the field at their intra soil differentiated introduction. Flow rate of SS was regulated with the help of the executive mechanism with the linear actuator and a reducer modified for work with the block of control and management according to the prescription map. Researches were conducted on purpose: estimating of operability of new SS, with the new drive for change of frequency of rotation of the coil; establishments of functional dependences between flow rate of SS, i.e. ability to provide its necessary range of change of doses at the differentiated introduction of fertilizers; estimates of quality of work of experimental SS for the differentiated introduction of mineral fertilizers. Researches were carried out both in laboratory and field conditions. Functional dependence of flow rate of SS on number of turns of coils is received. It is established also that flow rate of SS directly depends on percent of opening of the actuator and frequency of rotation of the sowing coil. The minimumtime of transfer from one to other dose equals 0.9 seconds. It is established that at SS with the three experimental coil devices unevenness of seeding between devices makes 4.5 persent. Instability of seeding does not exceed 3 persent. The maximum values of unevenness of seeding between 3 sowing devices and instability of seeding between replications are received when opening of the actuator was 40 persent, and frequency of rotation - 22 rpm, which nevertheless, also meet requirements for the sowing systems.